Research gaps in STEM-integrated project-based learning for critical thinking in physical education: A bibliometric analysis - Rahayu Prasetiyo; Arsika Yunarta; M. Zaim Zen (Universitas Sriwijaya, 2026)
Research Problems: Project-Based Learning integrated with Science, Technology, Engineering, and Mathematics (STEM-PjBL) has been widely recognized as an effective instructional approach for fostering higher-order thinking skills, particularly critical thinking. However, its application within Physical Education (PE) remains underexplored, and the current research landscape has not been comprehensively mapped. Research Objectives: This study aimed to identify research trends, collaboration patterns, conceptual structures, and research gaps related to STEM-integrated Project-Based Learning (STEM-PjBL) for enhancing critical thinking skills, with particular emphasis on its application in Physical Education, using a bibliometric approach. Methods: A bibliometric analysis was conducted using the Dimensions database. Publications were retrieved using the search query (